ANALYSIS OF TEACHERS APPROACHES IN HANDLING BULLYING BEHAVIOUR AMONG STUDENTS AT SDN 1 KAMBOWA, NORTH BUTON REGENCYRANKING FACTORS AFFECTING PUBLIC TRANSPORT MODE - Kosilah Kosilah; Krisnawati Krisnawati; Yurfiah Yurfiah; Toni Toni (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine teachers’ approaches in addressing bullying behavior among students at SDN 1 Kambowa, North Buton Regency. Bullying is a serious issue that can negatively affect students’ physical, emotional, and psychological development. This research employed a qualitative approach, with data collected through observation, in-depth interviews, and documentation. The participants included students, teachers, the school principal, and parents. The findings reveal that teachers applied several approaches to handle bullying, namely humanistic, preventive, intervention, restorative, and behavioristic approaches. Among these, the humanistic, preventive, and restorative approaches were the most frequently implemented in classroom management and daily school practices. These findings contribute to the field of educational psychology and classroom management by providing empirical insights into effective bullying prevention and intervention strategies. Furthermore, the results may serve as a reference for schools in developing comprehensive, sustainable, and relationship-oriented strategies to address bullying behavior.